The Effect of E-Trust and E-Satisfaction on Continuance Intention GoPay Users of the GoJek Application during the Pandemic - Assyifa Mulandar; Asep Muslihat (Peneliti.net, 2023)
As a result of the huge variety of different sources and knowledge available in this age of globalization, the fast-paced, instantaneous lifestyles required at all of society's levels are supported by an adoption of information systems. Customers have flocked to use online payment features as a result of the accessibility of numerous shopping platforms and the convenience of transactions. The Covid-19 pandemic's rise has also sparked changes in a number of areas, including the economy. According to the current situation, more people are definitely adopting digital platforms with all its advantages, benefits, and conveniences. These suggests that electronic money is well acceptable, especially in heavily inhabited urban regions where it may help stop the spread of the Covid-19 virus. As a result, the fierce competition in the market for digital wallets requires companies to be capable of developing and sustain high-quality electronic services. As a result, users of the application may feel more trustworthy. 100 people who currently use GoPay made up the sample for this study. This essential information was gathered through surveying. examination of data using linear regression. The findings demonstrated that E-Trust and E- Satisfaction significantly impacted GoPay consumers' intention to continue using the service.